Clinico-etiological characteristics of organizing pneumonia: A retrospective study - Marwah, Vikas (Lung India, 2021)
INTRODUCTION: Organizing pneumonia (OP) is an idiopathic interstitial pneumonia characterized radiologically by the patchy peripheral areas of ground-glass opacities and consolidation. It is commonly associated with a variety of conditions such as connective tissue diseases (CTD), drugs, infections, malignancy, radiation exposure, post-transplant, and other interstitial pneumonia. There are no specific clinical manifestations unless there is an underlying etiology. We present a series of such cases. AIMS AND OBJECTIVES: The aim of the study was to identify the clinical characteristics and etiological spectrum of patients manifesting radiologically with OP pattern. MATERIALS AND METHODS: This was a retrospective analysis of clinico-radiological profile and etiological diagnosis of 23 patients, who had a radiological diagnosis of OP during the period of January 2017–September 2019. RESULTS: Our patients presented with nonspecific symptoms of cough, fever, breathlessness, and occasionally with hemoptysis. The various etiologies identified were CTD (n = 4), infection (n = 2), drugs (n = 4), radiation (n = 1), chronic aspiration syndrome (n = 1), malignancy (n = 2), hypersensitivity pneumonitis (n = 1), and chronic heart failure (n = 2), and in majority (n = 7), no underlying etiology was evident and were labeled as cryptogenic organizing pneumonia. CONCLUSION: OP is an underdiagnosed entity and is associated with numerous diseases varying from pulmonary tuberculosis to malignancy. Identification of the underlying disease process is of paramount importance as it enables the treating physician to implement necessary therapeutic interventions.